Automation of Pick and Place Operation in Contact Lens Manufacturing - Abdul Wahab, Norhaliza; Thangaraj, Jeevaniswaran (ELEKTRIKA- Journal of Electrical Engineering, 2018)
The paper describes the design of an automation of pick and place operation in contact lens manufacturing. The contact lens pick and place robot is designed so that it replaces operators to pick and place contact lenses from cassette to PS-48 tray automatically. The microcontroller used in this project is Arduino Uno. Solidworks is a software used to create the design before fabrication. Actuators used in this projects are stepper motors due to their high precision in calculating steps to move by the overall system. C programming is used along with Arduino Integrated Development Environment, IDE in programming the movement of the robot.Â  For this project, the robot is controlled by pressing start and stop button. The automated lens pick and place robot is way better compare to humans since it is capable of reducing cycle time to complete the process by picking 7 lenses simultaneously. Moreover, the lens pick and place robot tend to reduce number of labours and improve the hygiene in contact lenses production. The lens pick and place robot has successfully helped to automate the process in contact lenses manufacturing. The goal of the design have been achieved whereby the robot manage to transfer the lenses from cassette to tray.